2018
DOI: 10.3390/ma11030437
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Fire Performance of Tubular Steel Columns with Membrane Protections for Prefabricated and Modular Steel Construction

Abstract: Experimental research was conducted to study the fire resistance of steel tubular columns used in prefabricated and modular construction. In order to achieve high-efficient prefabrication and fast on-site installation, membrane protections using board products and thermal insulation blankets are adopted as the favorable protection method. Three protected tubular columns were tested in a full-scale column furnace with axial load applied. The study variables were different membranes, including fiber reinforced c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The famous seismic loads were discussed by Gunawardena et al (2016a), where the authors discussed its effect on several elements and connections, and provided explanation to the behavior of the system. Fire performance of tubular steel columns was studied using various proofing materials; fiber reinforced calcium silicate (FRCS) boards, rock wool and aluminum silica (Fiberfrax), to check the fire rating in hours (Zhang et al, 2018). Further exploration of the benefits and challenges of using cold-formed steel sections as the main structure components were explored in the literature, particularly in Hong Kong.…”
Section: Structural Designmentioning
confidence: 99%
“…The famous seismic loads were discussed by Gunawardena et al (2016a), where the authors discussed its effect on several elements and connections, and provided explanation to the behavior of the system. Fire performance of tubular steel columns was studied using various proofing materials; fiber reinforced calcium silicate (FRCS) boards, rock wool and aluminum silica (Fiberfrax), to check the fire rating in hours (Zhang et al, 2018). Further exploration of the benefits and challenges of using cold-formed steel sections as the main structure components were explored in the literature, particularly in Hong Kong.…”
Section: Structural Designmentioning
confidence: 99%
“…The fire-resistant design of steel columns used in prefabricated modular construction was described in References [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on concrete-filled steel tube (CFST) members [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ] showed that the main parameters affecting the fire resistance limit of ST-RC columns are section perimeter ( C ), fire load ratio ( n ), slenderness ratio ( λ ), cross-sectional core area ratio α sc ( α sc = A sc / A 0 , where A sc is the core concrete area and A 0 is the area of the CFST), eccentricity e/r 0 ( r 0 = B /2), steel ratio ( α s ), yield strength of the steel tube ( f y ), yield strength of the steel bar ( f yb ), strength grade of the concrete ( f cu ), etc. The parameters of a typical example are given as follows: C = 2400 mm, n = 0.6, λ = 10, α sc = 0.25, α s = 0.15, f y = 390 MPa, f yb = 400 MPa, the strength grade of the concrete inside and outside the pipe is f cu = 40 MPa, and the initial eccentricity is L /1000.…”
Section: Parametric Analysismentioning
confidence: 99%